2020
DOI: 10.1177/1529100620920576
|View full text |Cite
|
Sign up to set email alerts
|

Education and Cognitive Functioning Across the Life Span

Abstract: Cognitive abilities are important predictors of educational and occupational performance, socioeconomic attainment, health, and longevity. Declines in cognitive abilities are linked to impairments in older adults’ everyday functions, but people differ from one another in their rates of cognitive decline over the course of adulthood and old age. Hence, identifying factors that protect against compromised late-life cognition is of great societal interest. The number of years of formal education completed by indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
388
8
23

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 685 publications
(470 citation statements)
references
References 264 publications
(371 reference statements)
51
388
8
23
Order By: Relevance
“…Education offers enriching experiences that improve domain-general cognitive skills such as processing speed, working memory, reasoning, and cognitive control [ 144 , 145 , 146 ]. It has been argued that the effects of education on cognitive functioning are evident across the lifespan, influencing individual differences in cognitive skills that appear in adulthood and persist with aging [ 147 ]. A few studies have investigated the effect of the level of education on cognitive abilities that are crucial for the fitness to drive.…”
Section: Discussionmentioning
confidence: 99%
“…Education offers enriching experiences that improve domain-general cognitive skills such as processing speed, working memory, reasoning, and cognitive control [ 144 , 145 , 146 ]. It has been argued that the effects of education on cognitive functioning are evident across the lifespan, influencing individual differences in cognitive skills that appear in adulthood and persist with aging [ 147 ]. A few studies have investigated the effect of the level of education on cognitive abilities that are crucial for the fitness to drive.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, possible that individuals with a higher reserve capacity also experience steeper decline once they begin to decline . Higher education has been suggested as protecting against cognitive decline in some studies (Christensen et al, 2009;Stern, 2002), but several recent studies have suggested that education increases cognitive performance, but does not protect against cognitive decline thereafter (Cadar et al, 2017;Lovden et al, 2020;Piccinin et al, 2013;Seblova et al, 2020).…”
Section: Interpretation Of the Main Findingsmentioning
confidence: 99%
“…For this purpose, an increasing number of studies have started to explore the role of socioeconomic conditions in childhood, across adulthood, or in late-life for interindividual differences in middle-aged and older adults’ cognitive functioning (e.g., [ 3 , 4 ]). In detail, low socioeconomic status or indicators of disadvantageous socioeconomic conditions across the life course, such as low parental socioeconomic conditions in childhood (e.g., [ 5 , 6 ]), low level of education [ 7 , 8 , 9 ] or low income [ 8 ], have a negative impact on late-life cognitive performance and are associated with cognitive decline in aging (but also see [ 5 , 10 , 11 ]). Conceptually, one explanation may be that favorable life course socioeconomic conditions are thought to be associated with more stimulating activities and thus being involved in building up of cognitive reserve throughout the lifespan [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, one explanation may be that favorable life course socioeconomic conditions are thought to be associated with more stimulating activities and thus being involved in building up of cognitive reserve throughout the lifespan [ 12 , 13 ]. This reserve could lead to better health in later life [ 14 ] and particularly, through structural and functional brain differences, buffer against cognitive impairments and early cognitive decline [ 5 , 10 , 11 ]. Indeed, different studies show that indicators of socioeconomic conditions are related to structural brain change (e.g., hippocampus volume and frontal cortex) as well as functional brain activity (e.g., differing activation in the network of prefrontal, frontal, hippocampus and parietal working memory areas), showing up at different life course stages and various cognitive functions (i.e., executive function, memory and language) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%